(3fSje GdnqUHG hfOje GdpqUHGs - (3GdQhej Gdecj GdegJGQj, GdegJGQ, EHQGgje Hf jhSa, J (B1071(3g`s
(3ChdgG (B:s
(3HSe Gddg CeGWJ dfG Yf CbGM GdOeGjK HeKd CSGQjY GdMbhb hGdYKGZK , bGd CHh eMeO Sgd Hf CMeO GdOjHGLj CfTOfG CHh HcQ eMeO Hf GdMSf Hf OQjO gPg GdbUjOI GdJGFjI HHZOGO aj CMO TghQ Cda hKdGKeGFI bhdg s
(3BNQgG (B:s
(3TgGH GdOjf GdefGRj hdg ajg (B: (3eZf dh JZfi jhe hUd dGhge Cfg djd GdSdje hdh Zfi Ydi GdcGSGJ jheG dCYji GdQGM Yf OaY Gdgehe , hdg ajg CjVG (B: (3SJ`CJj eG bO OgGfj ef JbHjd aj GdCZGfj bdJ EP Zfi YQGbG djJfj aj CUagGf s
(3JHUQI GdeDda (B:s
(3GdegJGQ LGAJ cdbH aj GdCYdGe haj fSNI fSje GdUHG GdeNWhWI (B, (3hcfSHI LGAJ aj eYLe GdeDdajf hgOjI GdYGQajfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\82s
(3gOjI GdYGQajf (B1\33s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs